Size of blood pressure reduction from renal denervation: insights from meta-analysis of antihypertensive drug trials of 4121 patients with focus on trial design: the CONVERGE report. Issue 21 (15th September 2013) - Howard, James P; Nowbar, Alexandra N; Francis, Darrel P
Abstract : Objective: 30 mm Hg drops in office systolic blood pressure are reported in trials of renal denervation, but ambulatory reductions are much smaller. This disparity is assumed to have a physiological basis and also be present with antihypertensive drugs. Design: We examine this office-ambulatory discrepancy through meta-analysis of drug and denervation trials, categorising by trial design. Patients (studies): 31 drug trials enrolling 4121 patients and 23 renal denervation trials enrolling 720 patients met the criteria. Results: In drug trials without randomisation or blinding, pressure reductions are 5.6 mm Hg (95% CI 2.98 to 8.22 mm Hg) larger on office measurements than ambulatory blood pressure monitoring (p<0.0001). By contrast, with randomisation and blinding, office reductions are identical to ambulatory reductions (difference −0.88 mm Hg, 95% CI −3.18 to 1.43, p=0.45). For renal denervation, there are no randomised blinded trial results. In unblinded trials, office pressure drops were 27.6 mm Hg versus pretreatment, and 26.6 mm Hg versus unintervened controls. By contrast, ambulatory pressure drops averaged 15.7 mm Hg across all trials. Among those where the baseline ambulatory pressure was not the deciding factor for enrolment (avoiding regression to the mean), ambulatory drops averaged only 11.9 mm Hg. Conclusions: Discrepancies in drug trials between office and ambulatory blood pressure reductions disappear once double-blinded placebo control is implemented. Renal denervation trials may also undergo similar evolution. We predict that as denervation trial designs gradually improve in bias-resistance, office and ambulatory pressure drops will converge. We predict that it is the office drops that will move to match the ambulatory drops, that is, not 30, but nearer 13.